From trial to real life: ten-year impact of a nutraceutical strategy on duodenal polyp burden in familial adenomatous polyposis - Calabrese, Carlo; Dussias, Nikolas Kostantine; Melotti, Laura; Russi, Sabino; Laurino, Simona; Crispo, Fabiana; Rizzello, Fernando (Frontiers in Oncology, 2026)
BackgroundFamilial adenomatous polyposis (FAP) is characterized by the early development of colorectal and duodenal adenomas. Although colectomy reduces the risk of colorectal cancer, duodenal neoplasia remains a leading cause of mortality.AimsTo assess the long-term efficacy of a nutraceutical blend containing phytoestrogens and insoluble fibers (Adipol) in reducing duodenal polyp burden in FAP patients.MethodsThis prospective cohort study followed 56 FAP patients for 10 years after completion of a randomised trial on Adipol. Importantly, post-trial treatment allocation was not randomised but based on patient choice. Patients freely choose one of four regimes: no therapy (Group 0), 3 months on/off (Group 1), 6 months on/off (Group 2), or continuous treatment (Group 3). Annual upper endoscopies evaluated duodenal polyp number and size.ResultsAt 120 months, the mean polyp count was significantly reduced in Group 3 vs Group 0 (8.2 ± 3.4 vs 25.1 ± 5.8; p<0.001). Similarly, maximum polyp size decreased more in Group 3 (3.9 ± 1.1 mm) compared to Group 0 (7.8 ± 1.9 mm; p<0.01). Groups 1–2 showed intermediate reductions proportional to exposure.ConclusionContinuous Adipol supplementation is associated with sustained reduction in duodenal polyp burden in FAP patients. Although the non-randomised, single-center design limits generalizability, these findings support nutritional chemoprevention as a valuable adjunct strategy in FAP. Multicenter randomised trials and biomarker studies are warranted.